2017
DOI: 10.5114/aoms.2016.60374
|View full text |Cite
|
Sign up to set email alerts
|

Clinical SYNTAX Score – a good predictor for renal artery stenosis in acute myocardial infarction patients: analysis from the REN-ACS trial

Abstract: A b s t r a c tIntroduction: In ST-elevation myocardial infarction (STEMI) patients, multisite artery disease represents a serious issue influencing evolution, outcomes and prognosis. We evaluated for the first time the power of the Myocardial Infarction SYNTAX Score (MI SS) and Clinical SYNTAX Score (MI CSS) as predictors for renal artery stenosis (RAS) in STEMI. We also stratified the study population according to the two scores, and identified the variables correlated with the higher score. Material and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Through the advent of modern antithrombotic therapy 2 , secondary prevention, and percutaneous coronary intervention (PCI) 3,4 , there has been a decrease in acute and long-term mortality due to cardiac causes; however, the one-year mortality due to ST segment elevation myocardial infarction (STEMI) is approximately 10% 5 . Thus, early risk stratification management has been utilized, and many risk predictive indicators have been applied to predict the short- and long-term prognosis of patients with AMI 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Through the advent of modern antithrombotic therapy 2 , secondary prevention, and percutaneous coronary intervention (PCI) 3,4 , there has been a decrease in acute and long-term mortality due to cardiac causes; however, the one-year mortality due to ST segment elevation myocardial infarction (STEMI) is approximately 10% 5 . Thus, early risk stratification management has been utilized, and many risk predictive indicators have been applied to predict the short- and long-term prognosis of patients with AMI 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…These predictors seem to be mostly preponderant. However, several other periprocedural indices related to technical aspects and maneuvers appear to be at least similarly influential for outcomes after coronary artery bypass graft interventions [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…e introduction of SYNTAX I and II scores [9], SYNTAX functional score [10] (based on coronary flow reserve), and Clinical SYNTAX score pointed out that it is a difficult task for a professional to decide/recommend a therapy on him/her individual own [11]. Moreover, recent studies suggested that intraobserver and interobserver variability when interpreting a coronary angiogram often results in inappropriate revascularization strategies [12][13][14].…”
Section: Introduction: Definitions and Timelinementioning
confidence: 99%